Stratégies de changement et politiques pénales - Normandeau, André (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
This article examines criminal justice policies and strategies of change, from agenda setting to decision-making, implementation and evaluation. Since 1960, change has been incremental, almost without regard to the predominant liberal or conservative ideological strategies. The author maintains, even if it is an old cliché, that reforming society is a better social policy than reforming the criminal justice system... if we have a choice!